2021
DOI: 10.3390/nano11102580
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Zero-Valent Iron Modified by Bentonite with Enhanced Cr(VI) Removal Efficiency, Improved Mobility, and Reduced Toxicity

Abstract: The aggregation of nanoscale zero-valent iron (nZVI) particles and their limited transport ability in environmental media hinder their application in environmental remediation. In this study, the Cr(VI) removal efficiency, transport performance, and toxicity of nZVI and bentonite-modified nZVI (B-nZVI) were investigated. Compared with nZVI, B-nZVI improved the removal efficiency of Cr(VI) by 10%, and also significantly increased the transport in quartz sand and soil. Increasing the flow rate can enhance the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Bentonite is a clay mineral collection of fine particles with high opening volume and particular active sites ( 17 , 79 ). Bentonite is a widely used porous adsorbent aluminum phyllosilicate clay with high adsorption capability, chemical and mechanical solidity, and unique inter-lamellar structural properties ( 80 , 81 ). The metal ion belongings, preliminary concentration, adsorbent quantity, and operational circumstances (contacting time, pH, temperature, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bentonite is a clay mineral collection of fine particles with high opening volume and particular active sites ( 17 , 79 ). Bentonite is a widely used porous adsorbent aluminum phyllosilicate clay with high adsorption capability, chemical and mechanical solidity, and unique inter-lamellar structural properties ( 80 , 81 ). The metal ion belongings, preliminary concentration, adsorbent quantity, and operational circumstances (contacting time, pH, temperature, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Metals like arsenic, chromium etc., interfere with various body processes and are toxic to many organs and tissues ( 82 ), thus leading to the generation of ROS, consequently creating oxidative stress in the body ( 46 ). Bentonite absorbs these toxic substances and acts as an ameliorating agent ( 80 , 83 ). In the present study, bentonite administration improved arsenic and chromium-treated broiler chicks compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…After 7 days of incubation on potato dextrose agar medium at 30 °C in the dark, spores were harvested and resuspended in sterile 0.05% Triton-X solution and then filtered through sterilized glass wool with a diameter of 5 to 10 μm. nZVI particles were prepared via liquid-phase reduction method as in our previous research …”
Section: Methodsmentioning
confidence: 99%
“…nZVI particles were prepared via liquid-phase reduction method as in our previous research. 27 The synergistic removal efficiency of Cr(VI) by P. oxalicum SL2 and nZVI was first investigated. A spore suspension (10 8 spores mL −1 ; 1.0%, v/v) was inoculated into potato dextrose liquid medium and preincubated for 48 h. Mycelial pellets were collected by filtration through a 0.25 mm sieve (approx.…”
Section: Fungal Strains and Experimental Designmentioning
confidence: 99%
“…1.35 g of FeCl3•6H2O, 0.28 g of bentonite, and 0.5 g of PVP were dissolved in a three-necked flask with 100 mL of ethanol-water solution. The solution was mixed with a mechanical stirrer for 10 min in N2 environment and 100 mL of 0.2 M KBH4 was added dropwise with a constant pressure separating funnel [123]. It was found that nZVI particles prepared by the reduction of Fe 3+ ions with NaBH4 are homogeneously dispersed on the bentonite surface.…”
Section: Bentonite Supported-nzvimentioning
confidence: 99%